Enzymatic ring opening polymerization of poly(globalide-co- -caprolactone) by means of supercritical technology and post functionalization by thiol-ene reactions - Guindani, Camila (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2018.